Seasonal shift in the effect of predators on juvenile Atlantic salmon (Salmo salar) energetics - Ward, Darren M. (Can J Fish Aquat Sci, 2011)
Predator effects on prey populations are determined by the number of prey consumed and effects on the traits of surviving prey. Yet, effects of predators on prey traits are rarely evaluated in field studies. We measured the effects of predators on energetic traits (consumption and growth rates) of juvenile Atlantic salmon (Salmo salar) in a large-scale field study. Salmon fry were released at 18 sites that encompassed a wide range in abundance of predatory slimy sculpin (Cottus cognatus). We sampled salmon after 21 and 140 days to measure salmon growth and estimate consumption using a mass-balance model of methylmercury accumulation. Salmon population density was reduced fivefold at sites with abundant sculpin. Over the early season, salmon consumed less where sculpin were abundant, suggesting that reduced foraging under predation risk contributed to predator-caused mortality. In contrast, over the late season, salmon grew more where sculpin were abundant, suggesting that compensatory growth at reduced salmon population density moderated predator-caused mortality. Predator effects on prey energetics can drive variation in survival and growth, with important consequences for population dynamics.